Usability Analysis of Interactive Display Technology for Academic Purpose - Kamila, Rania Hana; Dewi, Dyah Santhi (Jurnal Teknik ITS, 2024)
Interactive display investment cost is quite expensive. However, the display has not been utilized properly using the available features in there. This study will conduct the usability testing of interactive display in academic settings, do the usability analysis by focusing on efficiency, utility, and learnability of the interface, and provide recommendation of interactive display utilization by considering user experience (UX). According to testing activity, respondents did not face significant difficulties when performing usability testing task since the features and tools are resembled to similar application and software. However, since it is the first-time respondents use interactive display based on the requested tasks, there are some confusions on interactive display such as use of Screen Share to do presentation and some tools on Whiteboard and Annotate. Total score of System Usability Scale (SUS) is 66.61 which is categorized as marginal acceptable range and need to improve the usability of interactive display. Recommendation given are in the form of suggestions for using the interactive display in lecture activity to support interactive class.